PELAYANAN SOSIAL BAGI LANSIA TERLANTAR (Studi di Yayasan Al’Azis Kendari Sulawesi Tenggara) - Nasir, Irda Suci Ramadhani; Arsyad, Muh.; Jabar, Aryuni Salpiana (Universitas Halu Oleo, 2020)
This type of research used in this research is descriptive qualitative research with data collection techniques, interviews, observation, and documentation. While the informants in this study were the Chairperson of the Foundation, Secretary, Elderly associate, and abandoned elderly. The results of this study show that the existence of the Al'azis Foundation provides increased welfare for the abandoned elderly people such as the existence of Home Care Assistance Services and Elderly Social Care at home and Day Care and Elderly Posyandu which aims to improve the ability of the elderly productive or even non-productive ones. While, for the factors that affect the quality of elderly social services with the fulfillment of human resources and the infrastructure for the services provided as well as organized management and cooperation/partners undertaken which to produce mutual benefits.